Externalities and Macroprudential Policy - De Nicolo, Gianni (Staff Discussion Notes; Staff Discussion Notes, 2012)
This note overviews macroprudential policy options that have been proposed to address the systemic risks experienced during the recent financial crisis. It contributes to the policy debate by providing a taxonomy of macroprudential policies in terms of the specific negative externalities in the financial system that these policies are meant to address, and discusses their interrelations and some key implementation issues.